ANALISIS PENGGUNAAN GAYA BAHASA GURU PENDIDIKAN USIA DINI DALAM PROSES PEMBELAJARAN - Anggi, Handani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research describes the teacher's language style in the learning process, this study uses descriptive qualitative research to examine the language style used during the process of teaching and learning activities directly. The title raised in this study is "Analysis of the Use of Early Early Childhood Teacher Style Language Education in the Learning Process" The data obtained in this study are through studies and interviews directly to PAUD teachers. This research was conducted at PAUD Tunas Bhakti Pertiwi. The goal is to know how a teacher can use language to early childhood. As for what will be discussed in this study regarding the formation of polesidenton, tautology, rhetoric, metapora, tropen and metonimia. This study aims to determine the process of teaching a teacher to early childhood in the use of language style during the learning process.